Autosomal-Recessive Mutations in the tRNA Splicing Endonuclease Subunit TSEN15 Cause Pontocerebellar Hypoplasia and Progressive Microcephaly - Breuss, Martin W.; Sultan, Tipu; James, Kiely N.; Rosti, Rasim O.; Scott, Eric; Musaev, Damir; Furia, Bansri; Reis, André; Sticht, Heinrich; Al-Owain, Mohammed; Alkuraya, Fowzan S.; Reuter, Miriam S.; et al. (American journal of human genetics, 2016)
The tRNA splicing endonuclease is a highly evolutionarily conserved protein complex, involved in the cleavage of intron-containing tRNAs. In human it consists of the catalytic subunits TSEN2 and TSEN34, as well as the non-catalytic TSEN54 and TSEN15. Recessive mutations in the corresponding genes of the first three are known to cause pontocerebellar hypoplasia (PCH) types 2A-C, 4, and 5. Here, we report three homozygous TSEN15 variants that cause a milder version of PCH2. The affected individuals showed progressive microcephaly, delayed developmental milestones, intellectual disability, and, in two out of four cases, epilepsy. None, however, displayed the central visual failure seen in PCH case subjects where other subunits of the TSEN are mutated, and only one was affected by the extensive motor defects that are typical in other forms of PCH2. The three amino acid substitutions impacted the protein level of TSEN15 and the stoichiometry of the interacting subunits in different ways, but all resulted in an almost complete loss of in vitro tRNA cleavage activity. Taken together, our results demonstrate that mutations in any known subunit of the TSEN complex can cause PCH and progressive microcephaly, emphasizing the importance of its function during brain development.